Comparison of newly developed immuno-MS method with existing DELFIA® immunoassay for human chorionic gonadotropin determination in doping analysis. (March 2013) - Lund, Hanne; Snilsberg, Ann Helene; Halvorsen, Trine Grønhaug; Hemmersbach, Peter; Reubsaet, Léon
Background: The performance of a method for MS determination of human chorionic gonadotropin (hCG) was compared with a reference method currently used in World Anti-Doping Agency accredited doping laboratories – the DELFIA ® immunoassay.Results: A strong correlation was demonstrated for the serum samples. However, for the urine samples, DELFIA reported significantly lower quantitative hCG measurements than the MS method. This was explained by the relatively unstable content of intact hCG-heterodimer in urine during storage compared with in serum. Discrepancies observed for the urine analyses might be related to the molecular dissociation of intact hCG-heterodimer into free subunits during storage, and the direct effect this has on the intact hCG measurements provided by DELFIA. The MS method quantified both intact hCG and free hCG β-subunit simultaneously, and was thus less susceptible to this problem. However, both methods detected illicit levels of serum hCG an equally long time after administration.Conclusion: The presented work advocates the implementation of this MS method as a confirmatory method for hCG determination in doping laboratories.